Investigating Quantitative Status of Groundwater Resources in Kashan Plain, Perspective and Providing Appropriate Solutions - Hossein Khorasanizadeh; Hoda Ghasemieh; Mahdi Soleimani Motlagh; Mohammad Mirzavand (مهندسی منابع آب, 2023)
Abstract Introduction: In this research, the groundwater quantitative status in Kashan plain and its future perspective with emphasis on drinking water and health was investigated. Methods: For this purpose, water balance components and changes in storage volume of the aquifer were calculated using balance groundwater equation for the hydrological year 2017-2018. Findings: The results showed that the aquifer storage volume and the weighted groundwater level mean decreased more than 35 MCM and about 0.44 m, respectively. The analysis of the groundwater balance components indicated the total exploitation of Kashan plain aquifer was about 317.17 MCM in year 2017-18. Of this amount close to 88% (278.85 MCM) has been consumed in sectors of agriculture, green space, livestock and poultry, and evaporation from fishponds. The remaining 12 percent (38.32 MCM) has been used in the sectors of drinking, industrial, commercial, and service. In addition, the results of groundwater balance calculations revealed that the total discharge through the aquifer outlet was 34.87 MCM. Furthermore, the results of the scenarios used in the research indicated if the current trend of groundwater exploitation continues, the 5-year horizon of the aquifer (2018-2023) will worsen and the largest decline will occur in the western regions due to the high number of agricultural, drinking, and industrial wells. Therefore, several strategies were proposed to reduce the trend of aquifer decline, including reducing or eliminating the crop with high water requirement, reducing the gross irrigation water requirement, saving or infiltrating part of the runoff from the upper elevations, and constructing underground dam.